Differences in GPS variables according to playing formations and playing positions in U19 male soccer players - Borghi, S.; Colombo, D.; La Torre, A.; Banfi, G.; Bonato, M.; Vitale, J. A. (Research in Sports Medicine, 2021)
The aims of this study were 1) to investigate Global Positioning System (GPS)-based match physical performance according to players` playing position in three different playing formations (4-4-2, 3-5-2, 4-3-3) and 2) to analyse the differences in match performance between 1st and 2nd half. Twenty-three U19 elite male soccer players (age: 18±1 year, height: 1.80±0.04 m, body mass: 70.65±6.02 kg), categorized as Central Back (CB, n =5), Full Back (FB, n =4), Central Midfielders (CM, n =4), Wingers (W, n =3), Strikers (S, n =7), were monitored using 10Hz GPS during 31 competitive matches. The results showed that FB and W always had the highest very high-speed running distance and number of sprints in all playing formations. Significant decrease in all GPS variables was observed in the 2nd half of the match for all playing positions. Strength coaches should adopt specific training regimes in accordance with players` playing position.